Industrialised timber housing : from trial to production - Johnsson, Helena; Sardén, Ylva (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2008)
Increased cost and declining quality within the construction industry has resulted in a growing interest in industrialised housing construction. During the past 15 years Swedish timber housing has been in a start-up phase where the frame system has been adapted to fulfil the demands of the building regulations. Still, potential clients and building owners are uncertain of long-term financial costs and functional performance of timber houses. To take timber frame housing from the level of unique experimental projects to competitive industrialised production, manufacturers will have to face the challenge of convincing the market that timber is an equally sufficient frame material as the more traditional concrete and steel. This paper presents a summary and analysis of the research conducted within the field of industrialised timber housing at Luleå University of Technology. The summary is made through a literature review of research reports, theses, papers and statistic references. The results are put in relation to lean theories and the development of industrialised timber housing in Sweden, with the aim of establishing current knowledge and identifying future research needs. Industrialised housing in Sweden is a growing market with good potential to provide low-cost housing of good quality. The results points out organising the design process to support production, working on customer interaction and to providing information that decreases the uncertainty for future customers as challenges for the industrialised house builders. Further research within industrialised housing should address the quality concept in housing, reduction of uncertainties in customer relations and new business models. Support of the technical development with efficient stabilisation methods for high-rise buildings and simple joining methods during assembly is another important issue. Godkänd; 2008; 20080825 (heljoh)